Length-weight relationship and growth pattern of Sepioteuthis lessoniana lesson 1830 (Cephalopoda: Teuthida) from the Jaffná Lagoon, Sri Lanka - Sivashanthini, K.; Charles, G.A.; Thulasitha, W.S. (Asian Network for Scientific Information, 2009)
In the present study, length-weight regression equationg were derived for male and female S. lessoniana collected from the Jaffna lagoon, Sri Lanka in order to find out the regression parameters and growth pattern of this species. Sepioteuthis lessoniana (Lesson 1830) are one of the commercially important group of cuttlefishes and becoming an important model system for neurobiological and behavioral research. It appears to be the most adaptable species to the laboratory environment and there exist a need for detail study on length-weight relationship for this species. Such a mathematical equation enables conversion of one parameter in to another as is often required during monitoring field measurements. Regression coefficients were estimated by using the logarithms of the mantle lengths and the corresponding weights and the growth pattern of the species was also noticed. The curvilinear relationships of mantle length-weight relationships for male and female were TW = 0.200*ML2.477 and TW = 0.229*ML2.437, respectively. Covariance analysis for mantle length-weight relationships of males and females revealed that there is no significant difference (p>0.05) between male and female and hence a common formulae of TW = 0.213* TL2.459 was derived for S. lessoniana. Th 'b' values 2.477 and 2.4347 obtained for male and female, respectively indicate that the growth rate significantly differ from the ideal value '3′ and its growth said to be negative allometry.
Keywords: Allometric growth; Big fin reef squid; Cube law; Length-weight relationship; Sepioteuthis lessoniana